PENGGUNAAN LABORATORIUM MATEMATIKA SEBAGAI SUMBER BELAJAR MAHASISWA: STUDI KASUS DI LABORATORIUM MATEMATIKA IAIN MATARAM - Uswatun Hasanah; Susilahudin Putrawangsa; Siti Hikmatussani (Universitas Islam Negeri (UIN) Mataram, 2016)
The recent study intends to describe the usefulness of mathematics laboratory as learning resource for students at Mathematics Department IAIN Mataram. It is a qualitative descriptive research. The finding shows that the laboratory has been used relatively well as learning resource for students even though there are some obstacles faced by students. It is also found some alternate solutions to address the obstacles in order to maximize the usefulness of laboratory as learning resource.